1991
DOI: 10.1210/endo-129-5-2471
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Deprivation Induces Phenotypic and Functional Changes in the Thymus of Adult Male Mice*

Abstract: The functional immunological consequences of thymic regeneration after castration were studied in adult male C57Bl/6 mice. Phenotypic profiles of thymocytes present in the enlarged thymuses of castrate animals demonstrated a significant decrease in the proportion of thymocytes positive for the suppressor/cytotoxic phenotype (CD4-CD8+; P = 0.005). Thymic enlargement in castrate animals was accompanied by increased capacity of thymocytes to incorporate thymidine in response to Concanavalin A in vitro. Spleens fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(56 citation statements)
references
References 23 publications
3
52
0
1
Order By: Relevance
“…Despite the fact that in Cx rats a numerical increase in the TN subset was found, the proportion of these cells was reduced while the proportion and number of downstream DP cells (TCRab K , TCRab low and TCRab high ) was increased. These findings are fully consistent with the data that dihydrotestosterone treatment of adult Cx C57BL/6 mice produces an increase in the fraction of DN cells by nearly 35% accompanied by a decrease in the DP cell population (Olsen et al 1991). It may be assumed that the increase in cell number and proportion of DP subsets was derived from accelerated thymocyte transition from the TN subset, the latter being maintained by recruitment of precursor cells.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Despite the fact that in Cx rats a numerical increase in the TN subset was found, the proportion of these cells was reduced while the proportion and number of downstream DP cells (TCRab K , TCRab low and TCRab high ) was increased. These findings are fully consistent with the data that dihydrotestosterone treatment of adult Cx C57BL/6 mice produces an increase in the fraction of DN cells by nearly 35% accompanied by a decrease in the DP cell population (Olsen et al 1991). It may be assumed that the increase in cell number and proportion of DP subsets was derived from accelerated thymocyte transition from the TN subset, the latter being maintained by recruitment of precursor cells.…”
Section: Discussionsupporting
confidence: 91%
“…It may be assumed that the increase in cell number and proportion of DP subsets was derived from accelerated thymocyte transition from the TN subset, the latter being maintained by recruitment of precursor cells. Our present data indicate that even if precursor immigration into the thymi of Cx rats was increased, as has been suggested (Olsen et al 1991), it would not be sufficient to provide complete repopulation of this rapidly differentiating cell pool. Alternatively, the increase in cell number and proportions of downstream DP subsets may be due to augmented proliferation within these subsets, independent of the TN subset.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…The presence of the androgen receptor (AR) has been documented in lymphoid and nonlymphoid cells of thymus and bone marrow, but not in mature lymphocytes [24,25], suggesting that the major impact of androgens may be on the developmental maturation of T and B cells. Castration of male animals results in significant thymic enlargement and increase in thymus weight and thymocyte number [26][27][28], a phenomenon which is also observed in the setting of defective androgen action (the androgen-resistant testicular feminization mouse [29]. It has also been shown that androgen deprivation stimulates thymic T cell output and results in increased numbers of phenotypically naïve CD4+ and CD8+ peripheral T cells (approximately 2 weeks after castration) and enhances antigen-specific immune responses in postpubertal male mice [30].…”
Section: Gonadal Steroid Hormones Regulate Immune Responsesmentioning
confidence: 97%
“…In addition, androgen deprivation exerts a stimulatory impact on B-cell lymphopoiesis in the bone marrow (BM) [31,32], resulting in expansion of splenic and peripheral B-cell populations [33] and enhanced production of autoreactive antibodies [32]. Testosterone replacement in castrated mice, on the other hand, results in thymic regression and a significant decrease in thymocyte numbers, with a shift toward expression of mature thymocyte phenotypes, a decrease in double-positive (DP) phenotype (CD4+CD8+) T cells, and a relative predominance of the CD4-CD8+ suppressor/cytotoxic over the CD4+CD8-helper phenotype T cells [28]. Potential mechanisms include acceleration of thymocyte apoptosis [34], AR-mediated induction of downregulatory cytokines such as transforming growth factor beta (TGF-β) [35], or changes in thymocyte differentiation and maturation [36].…”
Section: Gonadal Steroid Hormones Regulate Immune Responsesmentioning
confidence: 99%